Expert Consensus Statement: Management of Dysphagia in Head and Neck Cancer Patients. (25th March 2023) - Kuhn, Maggie A.; Gillespie, M. Boyd; Ishman, Stacey L.; Ishii, Lisa E.; Brody, Rebecca; Cohen, Ezra; Dhar, Shumon I.; Hutcheson, Kate; Jefferson, Gina; Johnson, Felicia; Rameau, Anais; Sher, David; et al.
Abstract: Objective: To develop an expert consensus statement (ECS) on the management of dysphagia in head and neck cancer (HNC) patients to address controversies and offer opportunities for quality improvement. Dysphagia in HNC was defined as swallowing impairment in patients with cancers of the nasal cavity, paranasal sinuses, nasopharynx, oral cavity, oropharynx, larynx, or hypopharynx. Methods: Development group members with expertise in dysphagia followed established guidelines for developing ECS. A professional search strategist systematically reviewed the literature, and the best available evidence was used to compose consensus statements targeted at providers managing dysphagia in adult HNC populations. The development group prioritized topics where there was significant practice variation and topics that would improve the quality of HNC patient care if consensus were possible. Results: The development group identified 60 candidate consensus statements, based on 75 initial proposed topics and questions, that focused on addressing the following high yield topics: (1) risk factors, (2) screening, (3) evaluation, (4) prevention, (5) interventions, and (6) surveillance. After 2 iterations of the Delphi survey and the removal of duplicative statements, 48 statements met the standardized definition for consensus; 12 statements were designated as no consensus. Conclusion: Expert consensus was achieved for 48 statements pertaining to risk factors, screening, evaluation, prevention, intervention, and surveillance for dysphagia in HNC patients. Clinicians can use these statements to improve quality of care, inform policy and protocols, and appreciate areas where there is no consensus. Future research, ideally randomized controlled trials, is warranted to address additional controversies related to dysphagia in HNC patients.